The impact of COVID-19 pandemic on South Asian Stock Markets - Santos, Maria José Palma Lampreia dos (2023)
The main aim of this paper is to analyze the impact of the pandemic COVID-19 on the efficiency of capital markets in countries of South Asia, namely, the market efficiency of these stock markets in the pre and post-COVID-19 global wave. The methods include quantitative research and time series analysis. Information and data were collected from the stock indices of Pakistan (KSE), India (BSE), Bangladesh (DSE) and Sri Lanka (CSE) for the period from August 2018 to July 2021. The results confirm that all capital markets are efficient before the global outbreak. In a meanwhile, after the pandemic (COVID-19) all the financial markets present a low efficiency. Explain more in economic terms. This conclusion helps the regulators of markets and investors to take a step to make certain information in these economies, subsequently, returns of some stocks can be predictable and generate opportunities for abnormal earnings and arbitrage.